DESIGN OF AUTOMATIC DRIP IRRIGATION BASED ON CHANGE OF SOIL WATER CONTENT USING ARDUINO NANO MICROCONTROLLER - Rendy Pranata (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Formerly, most of Indonesian farmers only used a timer in an effort to set up drip irrigation scheduling. Thismethod is less effective in providing irrigation according to crop water requirement because it is only able toarrange the provision of irrigation basedon a predetermined time interval only, so that the excess or lack ofwatercan’t be controlled. This research makes an instrument which is able to overcome these problems, that is bydesigning an automatic control systemonregulating the provision of irrigationwater in drip irrigation by usingamicrocontroller thatworks based onchange of soilwater content. The parameters observed inthis studyare thechange of soilwater content, irrigationflowrate, bulk density of soil, and dropper flowuniformity. This study usesthree types of growingmedium, i.e. sand, red-yellowpodzolic soil, andmix soil with organic nitrofosfat fertilizer.Calibration tests showed a linear function, for sandmedium y = – 0.23x + 46.96 with percent error ± 5.22%, forred-yellowpodzolic soil andmix soilwith organic nitrofosfat fertilizermediumy = – 0.71x + 104.07with percenterror ± 2.92%. The results showed that the automatic control system is able to work well, i.e. turn on the pumpwhen soilwater content drops belowthe criticalwater contentand turnoff the pumpwhen soilwater content risesover the field capacity.